An Economic Feasibility Study for Establishing a Modern Community Pharmacy Integrated with an E-Ordering and Home Delivery Service: A Case Study in Al-Hawban Area - Taiz - Al-Samie, Ibrahim Saeed; Abdulmalik, Khaled; Al-Qubati, Ziyad Majid; Asaj, Mohammed; Nadhir, Mohanad (University of Science and Technology, Sana’a, 2026)
This study investigates the economic feasibility of establishing a modern community pharmacy integrated with e-ordering and home delivery services to the residents of Taiz city, specifically the Al-Hawban area and surrounding regions. The primary objective is to evaluate the market landscape and consumer needs through a descriptive-analytical approach. Data were collected using a multi-methodological framework, including a quantitative questionnaire distributed to potential customers, and qualitative interviews with pharmacy owners and industry experts. The Statistical Package for the Social Sciences (SPSS-23) was employed for data analysis. The findings reveal a robust and growing demand for pharmaceutical services driven by population density and an increasing preference for remote healthcare accessibility. Financially, the study demonstrates that the project is capable of achieving sustainable revenue growth and operational profitability. The estimated payback period is approximately three years and six months, which represents a competitive timeframe for similar healthcare investments. These results underscore the project’s viability as a promising investment opportunity, provided that efficient inventory and customer service management are maintained.